2021
DOI: 10.1108/ejtd-08-2020-0130
|View full text |Cite
|
Sign up to set email alerts
|

Impact of thriving at work on eustress and distress: career growth as mediator

Abstract: Purpose Thriving at work can affect eustress and distress differently, so the main purpose of this study is to determine the impact of thriving at work on stress and to extend the existing literature on stress by examining the mediating mechanism of career growth, which is one of the functions of human resource development, in the relationship between thriving at work and stress. Person environment fit theory is used to explain the framework. Design/methodology/approach Data were collected from 179 employees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Resilience is a dynamic progress of successful adaptability in facing a difficult situation, which contributes to the ability to cope well with adversity and change (McDonald et al, 2016 ). A previous study indicated that thriving had a positive impact on employability (Hennekam, 2017 ) and present stress (Um-e-Rubbab et al, 2021 ), suggesting that it helps individuals to attain success and wellbeing in their careers (Yang and Li, 2021 ). Thus, a person with a high-level resilience is more likely to have a greater self-efficacy and high sense of employability and post competency through indirect promotion of thriving at work, further contributing to greater calling.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Resilience is a dynamic progress of successful adaptability in facing a difficult situation, which contributes to the ability to cope well with adversity and change (McDonald et al, 2016 ). A previous study indicated that thriving had a positive impact on employability (Hennekam, 2017 ) and present stress (Um-e-Rubbab et al, 2021 ), suggesting that it helps individuals to attain success and wellbeing in their careers (Yang and Li, 2021 ). Thus, a person with a high-level resilience is more likely to have a greater self-efficacy and high sense of employability and post competency through indirect promotion of thriving at work, further contributing to greater calling.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Being an integrated state by a form of vitality and a sense of learning at work, thriving at work is regarded as a positive psychology, which contributes to both individual and organizational outcomes. At the individual level, thriving at work is positively related to positive health (Walumbwa et al, 2018 ), lower stress (Um-e-Rubbab et al, 2021 ), reduced burnout (Hildenbrand et al, 2018 ), and positive self-leadership (Abid et al, 2021 ). Moreover, thriving at work has a positive relationship with collective affective commitment (Walumbwa et al, 2018 ), career growth (Um-e-Rubbab et al, 2021 ), career adaptability (Jiang, 2017 ), creative behavior (Alikaj et al, 2021 ), voice behavior (Sheng and Zhou, 2021 ), innovative behavior (Wang et al, 2019 ), life satisfaction (Zhai et al, 2020 ), and so on.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a kind attitude creates a healthy and trustworthy environment (Islam et al, 2022). Leaders with paternalistic leadership result in greater employee performance (Faiz et al, 2022). Therefore, it could be concluded that leaders having paternalistic leadership qualities are having followers with positive attitudes and behavior.…”
Section: Paternalistic Leadership and Organization Citizenship Behaviourmentioning
confidence: 99%
“…Paternalism is commonly known as a type of paternalistic initiative which can be characterized as a standout amongst the most striking social qualities of Pacific Asian society's nations. The idea is more pertinent in nations, for example, Pakistan, Taiwan, Japan, China, India, and Korea (Faiz et al, 2022). The paternalistic leadership style has insignificant results for these nations but it is additionally common in nations of the Middle East Islam et al (2022) and Latin America (Osland and Osland, 2005).…”
Section: Introductionmentioning
confidence: 99%